(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
The study analyzed the socio-economic characteristics influencing farmers adoption of Information and Communication Technologies (ICTs) in Lokoja Local Government Area of Kogi State, Nigeria. A multi-stage random sampling technique was utilized to select 120 respondents. Descriptive and inferential statistics were employed for data analysis. Descriptive statistics such as percentages, frequency distribution and mean were used to organize and summarize data for objectives ii and iii. Probit model was used to analyze objective i and the hypothesis testing. The results of the estimated probit model of the factors affecting the adoption of ICT in the study area revealed that the coefficient of the sex and education status were the significant factors affecting the adoption of ICTs at five percent level of significance and 10 percent level of probability. 45.85 percent and 45.83 percent of the respondents acknowledged that poor access to ICT infrastructure, cost of hardware and software were the major problems affecting their adoption of ICT. It was found that 53.33% of the respondents acknowledged that ICT can broaden the knowledge of the user while 43.33% of the respondents prospected high income as one of the advantages of the ICTs, 39.16% were of the view that ICT is time effective while 25.83% of the respondents that ICT can save inputs. The results also revealed that mobile phones and radio set were the commonly adopted ICTs facilities in the study area and this was because of the cost of software and hardware, poor access to ICT infrastructure, constant power supply and low computer literacy level in the area. It was recommended that appropriate government agencies responsive for agricultural development should carry out thorough review about ICT facilities in the area with a view to increase and update them with modern ICTS.